Gestión administrativa para la reactivación económica del sector turístico san pablo del cantón valencia año 2021. propuesta alternativa. - Osorio Toscano, Josselyn Dalila (2022)
Theme: Administrative Management for the economic reactivation of the tourism sector San Pablo del Cantón Valencia. The present work called "Administrative Management for the economic reactivation of the San Pablo del Cantón Valencia tourism sector", will be developed as a contribution to the tourism sector of the town to face the results of the pandemic that has hit the sector very hard. taking into account the administrative level in relation to tourism development. To do this, we will proceed to search for reliable bibliographic information that allows supporting the development of the research, within the methodology the research is qualitative and quantitative. A convenience sampling will be carried out, being determined, the San Pablo Sector, among the research techniques to be applied are the survey, interview and direct observation, for which the application instruments will be elaborated; These instruments together will serve as a means to know the conditions that they are currently going through and based on that, a viable proposal will be proposed that will contribute to the solution of the problem through a plan of strategies aimed at publicizing the tourist benefits of the sector.